2023
DOI: 10.4028/p-vp9t5x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Alkali-Fluoride on the Photoluminescence Properties of Tb3+ Doped on Phosphate Glass Medium

Abstract: The effect of alkali fluoride on the photoluminescence properties of Tb3+ doped on the phosphate glass was discovered. However, the composition of the glass samples were 20Li2O–10AlF3–69P2O5–1Tb2O3 (LAPTb) and 20Li2O–10AlF3–10NaF–59P2O5–1Tb2O3 (LANPTb). To study optical properties were examined through their absorption and luminescence spectra. Luminescence spectra were investigated by photoluminescence. Characteristic luminescence bands corresponding to electronic transitions of terbium ions (Tb3+) were detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Radiative properties of Erbium doped Lithium Fluorophosphate glasses.Quantum efficiency in Table5show that Er2 glass also has the highest value. Based on these results, it can be concluded that EDLF glasses is superior for use in the development of NIR optical amplifier devices [16][17][18][19][20]…”
mentioning
confidence: 88%
“…Radiative properties of Erbium doped Lithium Fluorophosphate glasses.Quantum efficiency in Table5show that Er2 glass also has the highest value. Based on these results, it can be concluded that EDLF glasses is superior for use in the development of NIR optical amplifier devices [16][17][18][19][20]…”
mentioning
confidence: 88%